The effectiveness of wizer.me-assisted process writing instruction on students’ pentigraph composition skills: a quasi-experimental study in indonesian higher education - Adi Rustandi Adi; Rendy Triandy (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
The rapid integration of digital technologies in post-pandemic higher education has intensified the need for pedagogically grounded innovations in creative writing instruction. This study investigates the effectiveness of Wizer.Me-assisted process writing instruction in improving students’ pentigraph (short-short story) composition skills. Employing a quasi-experimental pretest–posttest control group design, the study involved 64 undergraduate students divided into an experimental group (n = 32) and a control group (n = 32) over a four-week intervention period. The experimental group received structured process writing instruction supported by multimedia prompts and rubric-based feedback within Wizer.Me, while the control group received conventional instruction. Data were analyzed using an independent samples t-test. Results revealed a substantial increase in the experimental group’s mean score from 49 (pretest) to 80 (posttest), compared to a more moderate improvement in the control group (50 to 60). The difference between groups was statistically significant, t(62) = 10.98, p < .001, with an exceptionally large effect size (Cohen’s d = 2.79). While the magnitude of improvement should be interpreted cautiously in relation to the assessment scale and contextual factors, the findings suggest that multimedia-supported digital scaffolding and rubric-mediated feedback can meaningfully enhance narrative coherence, idea development, and linguistic precision in short-form creative writing. This study contributes to the growing body of research on technology-enhanced language learning by demonstrating how interactive digital worksheets, when aligned with process writing pedagogy, can support creative writing development in higher education contexts.